Pengaruh Literasi Keuangan terhadap Keputusan Investasi dengan Financial Technology Sebagai Pemediasi di Kota Denpasar - Nyoman Angga Pradipa; Ketut Sinta Trisnadewi; Ni Made Ayu Dwijayanti (Juara: Jurnal Riset Akuntansi, 2023)
This study aims to determine the influence of other factors that can affect the relationship between financial literacy and investment decisions because there are many inconsistencies in the results of previous studies and in this study the mediating factor used is financial technology. This study uses a quantitative method with an associative approach. The respondents of this research are the millennial generation in the city of Denpasar. Data collection methods using questionnaires. Data is processed using the Smart PLS application. The update in this study is the use of financial technology as a mediating variable in explaining the research gap that occurred in previous studies. The results obtained are that financial literacy has no effect on investment decisions, financial literacy ad has a positive and significant effect on financial technology, and financial technology has a positive and significant effect on investment decisions. In this study it was also found that financial technology fully mediates the relationship between financial literacy and investment decisions.